Safe and Sustainable Use of Arsenic-Contaminated Aquifers in the Gangetic Plain: A Multidisciplinary Approach - Ramanathan, A (Springer, 2015)
This book offers a meaningful and practicable guide to better management of arsenic problems in the groundwater of the Gangetic Plain. It gathers contributions from distinguished researchers who have been actively working in the area for over a decade. The arsenic contamination of groundwater is a growing concern in the central Gangetic Plain, where the local population’s main sources of fresh water are surface water, groundwater and rain water; of these sources, only the last two generally meet the most important criteria for drinking water in their natural state. Natural geological changes are presumed to be the primary reason for arsenic contamination in this region. Further, most of the people living in this area have developed the habit of drinking water (groundwater) from the arsenic-contaminated tubewells in many parts of the region. As a result, many are suffering from arsenicosis and many more are at risk. Since the cause of arsenic contamination in groundwater still remains unclear, this book seeks to address the arsenic issue in this region by pursuing a holistic and systematic scientific approach. Accordingly, it delineates various sources, processes, hypotheses and remedial approaches that are needed to manage the arsenic contamination in the Central Gangetic Plain.